Management of Democracy Laboratory Development at SMAN 2 Samarinda - Jamil, Jamil; Marwiah, Marwiah; Munthe, Selly Aprilia; Agus Salim, Nur (Technium Social Sciences Journal, 2024)
Realizing a democratic society is a shared responsibility, especially in education, where learning in schools must play a role in preparing students as a generation of the nation who are ready to implement the democratic system mandated by the constitution. However, observations in the last few months, especially after implementing online learning for approximately two years, show a decline in the interest, enthusiasm, and motivation of students at State High School 2 Samarinda in facing the democratic system. To overcome this problem, this research aims to evaluate school management in developing a democracy laboratory for students at SMA Negeri 2 Samarinda. A qualitative approach was used in this research, by collecting primary data through field observations, interviews with school principals, teachers, and students, and secondary data from various reference sources such as books, articles, and scientific journals. Data analysis was carried out using the stages of data collection, data reduction, data presentation, and conclusion. The results of the research show that SMA Negeri 2 Samarinda has succeeded in implementing democratic development management at school, both in the classroom and in the school environment effectively. However, there are several characteristics of problems that become obstacles in the process of developing democracy laboratories.